Problematizing Blackness : Self Ethnographies by Black Immigrants to the United States. - Rahier, Jean Muteba (Crosscurrents in African American history., 2014)
This cutting-edge piece of scholarship studies the invisibility of the black migrants in popular consciousness and intellectual discourse in the United States through the interrogation of actual members of this community.